Analisis Fonologi Proses Zeroisasi Kata dalam Dialek Bahasa Bali di Desa Gegelang, Kecamatan Manggis, Kabupaten Karangasem - I Gede Pasek Arimbawa (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
This study examines the process of phoneme zeroing in words in the Balinese dialect of Gegelang village, Manggis sub-district, Karangasem regency, Bali. Zeroing is the removal of phonemes from a word without changing its meaning. Using a descriptive linguistics approach, data were collected through interviews with local residents and analyzed qualitatively. The results show various zeroing patterns, particularly in vowels and consonants, that contribute to the articulatory efficiency and phonological characteristics of the language used in this dialect. These findings are expected to provide new insights into the richness of regional language phonology and its implications for linguistic studies, particularly in the field of regional dialects